2019
DOI: 10.1186/s12880-019-0332-6
|View full text |Cite
|
Sign up to set email alerts
|

Power of computed-tomography-defined sarcopenia for prediction of morbidity after pancreaticoduodenectomy

Abstract: Background The goal of our study was to evaluate the current approach in prediction of postoperative major complications after pancreaticoduodenectomy (PD), especially symptomatic pancreatic fistula (POPF), using parameters derived from computed tomography (CT). Methods Patients after PD were prospectively collected in a database of the local department of surgery and all patients with CT scans available were assessed in this study. CT parameters were measured at the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 43 publications
0
35
1
Order By: Relevance
“…who were blinded to clinical data. Segmentation of CT data was performed using a custom made and recently published software tool . Briefly, the tool starts by standardizing the thickness of CT slices to 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…who were blinded to clinical data. Segmentation of CT data was performed using a custom made and recently published software tool . Briefly, the tool starts by standardizing the thickness of CT slices to 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…It varies among individuals as a result of differences in age, body density, and the degree of obesity. [5][6][7] In the face of critical organ shortage with increased utilization of marginal allografts procured from extended criteria donors (ECD), one of the most challenging clinical decisions in the liver transplantation setting is the optimal risk-quantification and the identification of high-risk recipients and/or donor-recipient combinations. 2,3 Besides the pure loss of muscle mass and function known as sarcopenia, qualitative structural changes, such as myosteatosis, characterized by the presence of inter-and intramyocellular fat deposition, 4 have been shown to be associated with reduced muscle strength and poor clinical outcomes in patients undergoing surgery for colorectal or pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Besides the pure loss of muscle mass and function known as sarcopenia, qualitative structural changes, such as myosteatosis, characterized by the presence of inter-and intramyocellular fat deposition, 4 have been shown to be associated with reduced muscle strength and poor clinical outcomes in patients undergoing surgery for colorectal or pancreatic cancer. [5][6][7] In the face of critical organ shortage with increased utilization of marginal allografts procured from extended criteria donors (ECD), one of the most challenging clinical decisions in the liver transplantation setting is the optimal risk-quantification and the identification of high-risk recipients and/or donor-recipient combinations. 8 In this regard, several clinical risk-assessment systems, using donor and recipient factors (eg, Balance-of-Risk or BAR score), have been developed over the past 10-15 years.…”
Section: Introductionmentioning
confidence: 99%
“…Amini et al reported higher risk of morbidity and complication was observed in patients with sarcopenia after curative resection for pancreatic adenocarcinoma [25]. Recently, both Nicolas and Minji et al have demonstrated mean muscle attenuation could be a promising parameter to predict complications and POPF after PD [6,7]. In addition to short-term results, long-term outcome also seems to relate to skeletal muscle conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, preoperative visceral obesity and sarcopenia have been shown associated with major complications in patients with pancreatic ductal adenocarcinoma (PDAC) [4,5]. Meanwhile, several studies began to reveal the close relationship between sarcopenia and postoperative pancreatic stula (POPF) in patients receiving PD [6][7][8]. However, the de nition and diagnosis of sarcopenia varied greatly in these studies and body composition differed in various population [9,10].…”
Section: Introductionmentioning
confidence: 99%